Restaurants and hotels expenditure in Polish households of the elderly - Piekut Marlena (Economics and Management, 2016)
The age of household members is an important factor for expenditures. The aim of the study is to investigate the level of expenditure on restaurants and hotels incurred in Polish households of the elderly in 2004-2013 and to identify the factors affecting such expenditures. The source of information used in the study was the household budget survey of the Central Statistical Office of Poland. The main methods used in this study were variance analysis and regression analysis. Restaurants and hotels expenditure increases every year together with their share in total household expenditure. The most important factors affecting the restaurants and hotels spending in Polish households of the elderly are: income per capita and the level of education of the head of the family. The study on consumption determinants at different groups leads to better understanding of consumer behavior circumstances and thereby ensuring a good quality of life for the people of the elderly.